(Draft) Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Bihar - Planning Commission (Planning Commission, 1985)
Subsidy is paid to the beneficiaries at various rates from 25% to cent-per-cent. The total subsidy is shared between the Central and State Governments in different proportions in different schemes. The one reproduced here is a weighted average. No allocation could be made since the subject was transferred to Energy Department in the month of June 1984. Expenditure is being made at present by the way of advance from the Bihar State Contingency Fund.
Bihar